Conduct and Accountability in Financial Services A Practical Guide. - English, Stacey (Bloomsbury Publishing Plc, 2018)
"Are you fully prepared for the implementation of the Senior Managers and Certification Regime across financial services firms and the related regulatory scrutiny on conduct and accountability? The 2008 financial crisis sparked major changes in global financial services regulation with attention and resources focused on the behaviour of firms and senior individuals and how they conduct their business. Regulatory reforms have been designed and implemented globally to address accountability and conduct in financial services. In the UK this has resulted in the Senior Managers and Certification Regime (SM&CR) being implemented across all FSMA-regulated firms. Conduct and Accountability in Financial Services: A Practical Guide provides comprehensive and expert guidance on how best to implement and comply with the SM&CR.In addition to acting as a guide to rule book requirements and regulatory expectations, it provides an in-depth look at the implications of the global focus on culture and conduct risk. A must-read text for all staff in UK financial services firms, professional associations, industry bodies, regulators, academics and advisers to financial services organisations, it covers: The context and regulatory basis for SM&CR including an overview of the development and roll-out of the regime Analysis of key changes from the previous 'approved person' approach Practical considerations for HR, internal audit and non-executive directors The increasing role of culture and conduct risk A practical overview of enforcement, penalties and learning lessons from enforcement actions Overarching principles of how to manage personal regulatory risk Regulatory relationship management The impact of technology An overview of related global developments Appendices with timeline, bibliography and a selection of other useful sources for senior managers Conduct and Accountability in Financial Services: A Practical Guide is on the syllabus reading list for the Regulation and Compliance exam offered by the Chartered Institute of Securities and Investments."--Bloomsbury Publishing.